Analysis of Vocabulary Improvement by Using Team Games Turnament at 4th Grader Students - Buntara Adi Purwanto; Suci Leonita (Prodi Sastra Inggris, Universitas Muhammadiyah Semarang, 2025)
This study aims investigates the effectiveness of cooperative learning using Team Games Tournament (TGT) in improving english vocabulary fourth-grade students’ MI Guppi Sumberwulan. Team Games tournament, where students are divided into small groups and compete in activities related to the subject matter, this game are believed to enrich the English learning experience and improve vocabulary retention. This study uses a qualitative approached with calassroom action research (CAR) method The research consists of two cycles, and each cycle consists of four stages, namely planning, action, observation, and reflection. The samples taken were twenty one students grade fourth MI Guppi Sumberwulan Wonosobo. The instruments used in the research were an observation checklist, a questionnaire, and test. The research results show that the TGT method can improve students' English vocabularybased on observation checklist data, increasing from 60% to 70% and in cycle 2 to 86%. The test data increased from 64,96 to 74,48 and in cycle 2, it increased to 87,53. The increase in questionnaire data can be seen from the increase in the number of students who answered agree and strongly agree with each statement given. Which shows improvements in student English vocabulary, student behavior, and student English vocabulary abilities. From the results of the data above, it can be concluded that implementing the TGT method can improve students’ English vocabulary.